Penerapan Pembelajaran Kooperatif Tipe Jigsaw sebagai Wujud Penerapan Nilai-Nilai ANEKA dalam Proses Belajar Mengajar - I Wayan Gede Suarjana; Siti Fathimah (Institut Pendidikan Indonesia, 2021)
The purpose of this study is to determine the basic values that must be owned and understood by Lecturers as State Civil Apparatus and to actualize the basic values of ASN through the use of the jigsaw learning method. Through this habituation activity, it is hoped that it can be a measure of success in improving public services. There are 6 supporting activities chosen to solve the selected core issues, namely making and packaging learning plans that focus on student activity. delivering learning materials using the Jigsaw cooperative learning model, compiling questions in varied forms, carrying out formative evaluations, checking student test/test results, and analyzing student test/test results. The research finding is that the actualization of ANEKA values has been successful in motivating and increasing students' understanding and activeness with innovative learning models in the Basic Occupational Health and Safety course. This increase in understanding can be seen from the results of evaluation tests in participating in learning during actualization and increasing student activity during learning time. By analyzing the results of the evaluation, it is known that student learning completeness with predicates is very good at 35%, good at 50%, and quite good at 15%.